2009
DOI: 10.1111/j.1477-2574.2009.00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Is isolated Roux loop pancreaticojejunostomy superior to conventional reconstruction in pancreaticoduodenectomy?

Abstract: Isolated Roux loop pancreaticojejunostomy is not superior to conventional PJ; instead, it increases the duration of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 16 publications
2
47
1
2
Order By: Relevance
“…Patients with POPF after IRPJ resumed oral feeding without any increase in the amount of leak and demonstrated a principal advantage in the absence of delayed gastric emptying. However, some studies have found no significant difference in either of these factors …”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Patients with POPF after IRPJ resumed oral feeding without any increase in the amount of leak and demonstrated a principal advantage in the absence of delayed gastric emptying. However, some studies have found no significant difference in either of these factors …”
Section: Discussionmentioning
confidence: 95%
“…Isolated Roux loop PJ was first reported in 1976 by Machado et al . In many studies, IRPJ did not avoid POPF but did decrease leak‐related morbidity and mortality . In a prospective randomized study of 216 patients, Ke et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7). Aucun essai randomisé n'a été rapporté sur le rôle de l'anse en Y et l'analyse de la littérature est compliqué par l'association éventuelle de l'anastomose biliaire sur la même anse en Y. Plusieurs travaux comparatifs rétrospectifs ont été publiés récemment [36][37][38][39], incluant pour certains plus de 100 patients par groupe [38] qui ne montrent pas de réduction ni du taux de FP ni de leur gravité. Aucun essai randomisé n'a été rapporté sur le rôle de l'anse en Y et l'analyse de la littérature est compliqué par l'association éventuelle de l'anastomose biliaire sur la même anse en Y. Plusieurs travaux comparatifs rétrospectifs ont été publiés récemment [36][37][38][39], incluant pour certains plus de 100 patients par groupe [38] qui ne montrent pas de réduction ni du taux de FP ni de leur gravité.…”
Section: Anastomose Pancréaticojéjunale Sur Une Anse Isoléeunclassified